Surgical and oncologic approach to leiomyosarcoma of the inferior vena cava: A case report - Feleke Hailmariam Maniso; Mathewos Assefa Woldegeorgis; Hawi Furgassa Bedada (Clinical Case Reports, 2024)
Key Clinical Message LMS of IVC needs a multidisciplinary approach. Surgical excision with free margin is the cornerstone of management. Upon case‐by‐case selection, adjuvant chemotherapy may play a role in better oncologic outcome. Abstract Leiomyosarcoma (LMS) of the inferior vena cava (IVC) is a rare form of mesenchymal origin malignancy with less than 400 cases reported to date. Surgery is the mainstay of management but it requires vast experience in vascular and visceral surgery to attain a free tumor margin. Subsequent adjuvant treatment with chemotherapy and radiation remains as an area of gray zone. We report the case of a 61‐year‐old man with an 8‐month history of abdominal pain. Upon physical examination, an ill‐defined mass over the right side of the lower abdomen and bilateral lower extremity edema were detected. Abdominal ultrasound with Doppler revealed a right‐side retroperitoneal mass invading the IVC with extensive venous thrombosis for which anticoagulation was initiated. Computed Tomography of the abdomen revealed a huge heterogeneously enhancing mass involving the whole length of the infrarenal IVC obstructing the IVC lumen with collateral veins draining through the paralumbar veins and inferior epigastric veins bilaterally. With a top differential of primary IVC LMS, a midline longitudinal laparotomy was performed with an intraoperative finding of a tumor arising from the infra‐renal IVC which was excised. Gore‐Tex graft was used to reconstruct the IVC. There was an injury to the right common iliac artery and it was repaired by end‐to‐end anastomosis. Histopathology confirmed a high‐grade LMS of the IVC and surgical margin status was unknown. He was given adjuvant Chemotherapy consisting of Doxorubicin and Dacarbazine. He has been on follow‐up at the Oncology side with a good performance status.